The World Powerlifting Records - a new story - Stetsenko A.I (Kharkov National Pedagogical University, 2012)
Due to changes in weight classes in powerlifting there is a need for a new registration records. The world records standards approved by the IPF, have several disadvantages, are resulted. Lifters exceeded or have gained only 41.8% of standard records during the 2011 competition under the new rules, with some exercises, absolutely all of the standards have remained elusive. Simultaneously, documented cases of lifters were able to make 10 or more amendments to the existing record standard. It is well-proven that a dynamic setting world records is illogical, inconsistent and requires a revision of existing.